2020
DOI: 10.1055/a-1236-3217
|View full text |Cite
|
Sign up to set email alerts
|

Safety and outcomes of endoscopic ultrasound-guided drainage for malignant biliary obstruction using cautery-enabled lumen-apposing metal stent

Abstract: Background and study aims There is increasing evidence to suggest that EUS-guided biliary drainage (EUS-BD) is a safe and effective treatment alternative for patients with malignant biliary obstructions (MBOs) after failed endoscopic retrograde cholangiopancreatography. Patients and methods We performed a retrospective analysis of data prospectively collected from patients with MBO who underwent choledochoduodenostomy (CDS) or gallbladder drainage (GBD) between August 2016 and June 2020 using the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Available data from retrospective studies, randomized controlled trials (RCTs), and meta-analyses have reported comparable technical and clinical success rates for EUS-CDS and EUS-HGS ( Tables 1 s and 2 s , see online-only Supplementary material) 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 . Pooled data from studies directly comparing these two techniques in 303 and 329 patients respectively, estimated technical and clinical success rates of 94 % and 88 % for EUS-CDS, and 96 % and 87 % for EUS-HGS ( Table 3 s ) 10 18 19 30 38 39 40 41 42 43 44 45 46 .…”
Section: Biliary and Pancreatic Duct Drainagementioning
confidence: 95%
“…Available data from retrospective studies, randomized controlled trials (RCTs), and meta-analyses have reported comparable technical and clinical success rates for EUS-CDS and EUS-HGS ( Tables 1 s and 2 s , see online-only Supplementary material) 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 . Pooled data from studies directly comparing these two techniques in 303 and 329 patients respectively, estimated technical and clinical success rates of 94 % and 88 % for EUS-CDS, and 96 % and 87 % for EUS-HGS ( Table 3 s ) 10 18 19 30 38 39 40 41 42 43 44 45 46 .…”
Section: Biliary and Pancreatic Duct Drainagementioning
confidence: 95%
“…Table 1 shows recent studies regarding EUS‐CDS (published in the last 5 years [between 2015 and 2020], and including over 15 cases). 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 The main indication is failed ERCP, but recent studies have tried to evaluate the clinical efficacy of EUS‐CDS for primary drainage. 8 , 13 , 19 , 20 , 26 Technical success rates of EUS‐CDS range from 88.8% to 100%, and the clinical success rate ranges from 85.5% to 100%.…”
Section: Overview Of Recent Clinical Outcomes Of Eus‐cdsmentioning
confidence: 99%
“…The use of LAMS has shown to decrease recovery time, costs, and duration of hospital stay, compared to previous treatments [ 2 ]. There are several main indications for LAMS placement, such as for the treatment of pancreatic pseudocyst, walled-off pancreatic necrosis (WOPN), malignant biliary obstruction, cholecystitis and gastric outlet obstruction (GOO) [ 3 , 4 , 5 , 6 ]. LAMS can be also placed through the meshes of an indwelled duodenal self-expandable metal stent, during the same procedure [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%